Poder, práticas e relações políticas: políticos e eleitores em Aracoiaba-CE - Nogueira, Carlos Antonio Ferreira (2021)
This research consists of an analysis of how politicians relate to each other and to their voters in the small municipality of Aracoiaba, in the interior of the state of Ceará, Northeastern Brazil. The objective is to enter the universe of meanings and senses in an attempt to interpret the policies and practices linked to this field. During the research, it was possible to identify a place marked by political-elector relations, in a scenario permeated by the universe of so-called “helps”, which generate bonds and dependence between them. Political-political relations seem to be established from the exchanges of support in which local politicians support candidates for the Legislative Assembly and the National Congress who, in order to obtain votes, depend on the support of political leaders in the municipality. These, in turn, establish links of dependency and “help” with voters and how to obtain votes for candidates they support. This set of nexuses thus seems to forge an extensive and dense network of interdependence that connects politicians and voters in a kind of system or circuit capable of making and undoing according to the links existing in this network. The survey also identified changes in the media pattern of electoral campaigns and communication of political leaders with voters and voters in general. In addition to verifying a concurrence in the ways of doing politics marked by personality together with the other that can develop from values and preferences linked to political parties and spectrums. For this research, semi-structured questionnaires were identified and conversations with politicians and members of political groups were carried out, participant observation, records in field diaries and analyzes of rituals and events such as "meetings", "visits", "rallies", "Progressions" were carried out.”, “carreatas”, in short, mobilizations around candidacies, in addition to photographic records and audio recordings, in the period from 2016 to 2020, in the aforementioned municipality.